A Class of Generalized Differential Operators with Infinitely Many Discontinuous Points - Yurong Li (Abstract and Applied Analysis, 2014)
We define a class of differential operators T which have infinitely many discontinuous points, and investigate the kernel of T in terms of operator theory. It is shown that the solutions of T have exponential behavior, and the dimension of the kernel is given.